Historia clínica electrónica interoperable: El caso de Colombia - Sánchez-Duque, Jorge A.; Paredes-Mondragón, Carol V.; Ramírez-González, María C.; Galvis-Acevedo, Sebastián (Revista del Cuerpo Médico Hospital Nacional Almanzor Aguinaga Asenjo, 2022)
Carta al editor (sin resumen)